NILAI PENDIDIKAN DAN MORAL DALAM NOVEL “DENDAM” SI YATIM-PIATU KARYA SINTHA ROSSE - Supriyantini Supriyantini; E Zaenal Arifin (Universitas Nasional, 2019)
ABSTRACTNovel Dendam si yatim Piatu by Sintha Rose is a work of the writer's creativity in describing the life of themain character. The study aims to describe (a) educative values and (b) moral values in this novel. Themethod used is descriptive qualitative and literature study. The theoretical framework in this study is thenature of literature, the benefits of literature for teaching literature. The findings of this study is the existanceof the educative values cover the value of education, faith, intellectual, psychology, moral, and the value ofphysical education. Human values that elevate standard and the dignity of the main character from zero tohero. The faith and intellectual values go together and complement each other. Allah will exalt in degreethose of you who believe and those who have been granted. The moral values found in this novel arereligious, individual, and social values. The main character of this novel has a